Low-order models for the calculation of compressor sub-idle characteristics - Righi, Mauro; Ferrer-Vidal, Luis E.; Allegretti, Alessandro; Pachidis, Vassilios (ISABE, 2019)
This paper focuses on the development of low-order models for the generation of compressor sub-idle characteristics via numerical simulation of an axial-flow compressor at sub-idle conditions. A through-flow code using body forces developed by Cranfield University is used as a framework to test three new methods to model blade row performance under sub-idle conditions. The first method is a simplified analytical model of a separated blade passage, originally developed to model reverse flow through the passage. The method consists of a modification to the body forces employed by the code and can be easily adapted to model the sub-idle operating condition. The second method is a set of pressure loss and deviation angle correlations developed at Cranfield University specifically for sub-idle conditions. A third approach makes use of the deviation angle correlations along with the modified body-force method, resulting in a hybrid approach. These three methods are implemented in the through-flow code to obtain low-order models that are then used to generate compressor characteristics under locked rotor and windmilling conditions. The code created is able to generate compressor characteristics throughout the sub-idle operating regime in a few minutes. The low-order model results are compared against experimental data from a sub-idle compressor rig and CFD RANS simulations of the same compressor. The generated characteristics show promising results, with only minor calibration required for the numerically calculated characteristics to match those generated via experiment.
Keywords: Axial Compressors; Sub-idle conditions; Performance; Simulation and Design